Performance evaluation of decentralised spatio-centric and traditional MQTT messaging protocols in a SUMO simulation for taxi operations in Stellenbosch - Folscher, Alida (Stellenbosch : Stellenbosch University, 2025)
Folscher, A. 2025. Performance Evaluation of Decentralised Spatio-Centric and Traditional MQTT Messaging Protocols in a SUMO Simulation for Taxi Operations in Stellenbosch. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/9b9da02c-be27-4ebc-866c-c10a031b4dfd